David Versus Goliath: The Competitiveness Of Africa’s Local Enterprises In The Global Economy - OGBOR, John O.; IYAMABHOR, Martins; AWOSIGHO, Onome Precious (Archives of Business Research, 2021)
As a result of the dynamics of globalization, the variegated economies of the world have become more homogenous, integrated, interrelated and interdependent. However, rather than becoming a veritable player in a network of interrelationship and interdependency, the African economy has increasingly become a powerless spectator in the theatre of globalization. Although there is a great deal of literature and research in this area of international business, most of it has concentrated on the multinational corporations and their effects on the host country’s economy. Research and literature in this field have mainly looked at protective measures and subsidies as the way out of foreign competition; it has rarely addressed competitive strategic responses of local firms to foreign multinational corporations operating in the local economies. Anchored on the resource-based view of the firm and the network interaction theory, the paper provides an alternative framework or a paradigm shift for analyzing the competitive options available to Africa’s local firms in a global market. From this paradigm shift, the competitive advantages of Africa’s local firms are conceptualized to be (i) a function of firm specific assets and (ii) the prevailing home market conditions. The method of inquiry adopted in this paper is textual deconstruction. The major contribution of this study to the existing globalization discourse is its shift of focus from the multinational corporation to the analysis of global competition from the perspective of the competitiveness of enterprises in less developed economies such as Africa. The suggested framework and paradigm shift can also be used by scholars to map strategic options for local enterprises in selected markets. Future research can subject the suggested framework to empirical scrutiny to see how well the arguments hold.